Educational Intervention Strategies in the English Language Classroom for Students With Attention-Deficit/Hyperactivity Disorder in Primary Education - Moro-Ramos, Sandra (2021)
Introduction. This article analyzes the pedagogy of an ESL teacher in a primary school. Objective. This investigation aims to evaluate the instruction of the ESL teacher, more specifically to analyze the measures implemented with attention-deficit/hyperactivity disorder (ADHD) learners. All these ideas outline a realistic model in the paradigm of teaching and learning English as a second language with ADHD students. Methods. Under a desk research scope, the teacher’s instruction is reviewed, several methodologies are analyzed and put into practice, and the educational practice is modified to adjust the intervention procedures to ensure that all pupils, with or without ADHD, learn ESL. Results. As a result of this study, several techniques are recommended to teach ESL to ADHD students. Discussion. Based on the fact that ADHD is a neurobiological disorder where the impact in every person diverges and the possible problematic areas differ from one to another, several activities and techniques are proposed to provide these individuals with the skills they need to acquire English as a second language. Additionally, this article also proposes two cognitive training self-instruction models for children, with and without ADHD, for oral and written activities in ESL.